Effective sludge dewatering using Moringa Oleiferaseed extract combined with aluminium sulfate - Abdulazeez, Qabas Marwan; Jami, Mohammed Saedi; Alam, Md Zahangir (Asian Research Publishing Network (ARPN), 2016)
This research aims to find an optimum mixture ratio that consists of natural and chemical coagulants, and using it for sludge dewatering. Moringa oleifera seed extract by NaCl solution (1 M) was used as natural coagulant due to its characteristics such as availability, low cost, biodegradable, and it is environmentally friendly. This natural coagulant was combined with aluminium sulphate Al2(SO4)3.18H2O (alum) as chemical coagulant. Sludge samples were prepared from kaolin suspension (5% w/v) with distilled water. The purpose ofthe mixed coagulant is to produce a mixture with low chemical content and high dewatering efficiency, and to involvethe natural coagulant in sludge dewatering process. The use of mixed coagulant can achieve less hazardous impacts to human health and environment. Optimization of process conditions (the first optimization) was done using three factors: M. oleiferadosage, pH, and mixing time. The second optimization was done to determine the optimum mixture ratio between alum and M. oleifera using Quadratic Mixture Model optimization. This optimization (mixture ratio optimization) was run under the same optimum values of dosage, pH, and mixing time obtained from the first optimization to optimize the coagulation efficiency of M. oleiferaseed extract. The specific resistance to filtration (SRF) was used as response for both optimization steps, and the results were analysed using Analysis of Variance (ANOVA) approach by Design-Expert v9 software. Results showed that the optimum SRF value obtained from the first optimization was 1.1E+11 m/kg at dosageof 235.58 mg/L, pH of 6.5, and mixing time of 21.2 min at R 2 = 95.8%. For the second optimization, the optimum SRF value was 0.8E+11 m/kg for the ratio of 50:50 for alum and M. oleiferaseed extract. At this ratio, dewatering efficiency was the same as the efficiency of alum alone (0.8E+11 m/kg). Using mixed coagulant at ratio of 50:50 for alum and M. oleiferaseed extract, sludge dewatering efficiency can be high with 50% elimination of alum use.